Hubungan Karies Gigi dengan Status Gizi pada Anak Usia 6—14 Tahun di Pesantren - Laura Taniela Salsabil; Meta Maulida D; Agung F Sumantri (UNISBA Press, 2022)
Abstract. Dental caries that hit the pulp cavity can cause pain in the teeth and can disrupt the process of mastication that will affect the decrease in the frequency of eating and cause growth and development disorders in children. The purpose of this study was to analyze the relationship of dental caries with nutritional status in children aged 6-14 years at Islamic Boarding School. The study is observational analytics with a cross-sectional approach method, and sampling-based on consecutive sampling techniques, and analyzed with the Chi-square test. The research was conducted at Islamic Boarding School, in April 2021. The study data were obtained from the results of the filling data form for dental caries assessment and physical examination from measuring height and weight for BMI measurements to 35 children who met the inclusion criteria. The final results showed a dental caries incidence rate of 91.4%, and children with normal nutritional status as much as 65.7%. The results of the analysis of dental caries and nutritional status data showed a value of p = 0.341 (p>0.05) which means there is no significant relationship between dental caries and nutritional status. In this study, the incidence of dental caries is still very high but most children have a normal nutritional status. Nutritional status and dental caries are not one of them. Abstrak. Karies gigi yang mengenai rongga pulpa dapat menyebabkan rasa sakit pada gigi dan dapat menimbulkan gangguan proses mastikasi yang akan berpengaruh terhadap penurunan frekuensi makan, dan menyebabkan adanya gangguan pertumbuhan dan perkembangan pada anak. Tujuan penelitian ini adalah untuk menganalisis hubungan karies gigi dengan status gizi pada anak usia 6—14 tahun di Pesantren. Penelitian ini merupakan analitik observasional dengan metode pendekatan cross sectional, dan pengambilan sampel berdasarkan teknik consecutive sampling, serta dianalisis dengan uji Chi-square test. Penelitian dilakukan di Pesantren, pada bulan April 2021. Data penelitian diperoleh dari hasil formulir data isian untuk penilaian karies gigi dan pemeriksaan fisik dari mengukur tinggi badan dan berat badan untuk pengukuran IMT kepada 35 anak yang memenuhi kriteria inklusi. Hasil akhir penelitian menunjukkan angka kejadian karies gigi sebesar 91,4%, dan anak dengan status gizi yang normal sebanyak 65,7%. Hasil analisis data hubungan karies gigi dan status gizi menunjukan nilai p=0,341 (p>0,05) yang berarti tidak terdapat hubungan yang signifikan antara karies gigi dengan status gizi. Pada penelitian ini angka kejadian karies gigi masih sangat tinggi tetapi sebagian besar anak memiliki status gizi yang normal. Status gizi dan karies gigi bukan salah satunya.